Econometric Approach of the Scenarios regarding the Impact of the Consumer's Empowerment and Companies' Responsibility for Environment Sustainability on the Electricity Market Performance - Camelia I. Lungu; Cornelia Dascalu; Chirata Caraini; Erica C. Balea (Amfiteatru Economic Journal, 2014)
Energy is a major component of the economy, both as a sector in itself and as an input factor to all other economic activities. This sector is facing major challenges regarding increasing oil prices, severity of climate change or extremely complex implications of the global financial crisis. Organized as an empirical study, based on econometric analysis supported by a rigorous literature review, the paper studies possible correlations between the performance of electricity market, renewable resource consumption, consumers' behaviour, the influence of economic environment and economic development. It also aims to encourage a new and wider research framework regarding the implications of economic policies' use on consumers' perception. The results of the study indicate that the early stage of renewable energy use and the prospect of influencing the consumer behaviour in a way to increase the market performance, through the development of strategies oriented towards sustainable energy consumption, can have a positive impact on companies' responsibility. It is concluded that consumers' empowerment stimulates competition, raises efficiency and rethinks companies' strategies for environment sustainability.
Keywords: D12; M14; Q42; Q43; Q47; Q56; 330; consumers' empowerment; corporate responsibility; sustainable environment; market performance; renewable energy; econometric scenarios analysis